Two new species of Piaroa (Arachnida: Schizomida, Hubbardiidae) from Colombia, with comments on the genus taxonomy and the flagellar setae pattern of Hubbardiinae - Moreno-González, Jairo A.; Delgado-Santa, Leonardo; de Armas, Luis F. (Zootaxa, 2014)
Two new species of the genus Piaroa Villarreal, Tourinho & Giupponi, 2008, P. escalerete sp. nov. and P. bacata sp. nov. are described from Valle del Cauca, and Cundinamarca departments, Colombia, respectively. The female flagellum is fully illustrated for a Piaroa species for the first time; the generic diagnosis is also emended and the relationships of the new species with those previously described are discussed. New characters for Piaroa species, a new nomenclature for the chitinized arch and a reinterpretation of the Hubbardiinae flagellar setae pattern are proposed. A distribution map of the known species of Piaroa is provided.